Female Smallholders in the Financial Inclusion Agenda - Hernandez, Emilio; Bin Humam, Yasmin; Ciacci, Riccardo; Benni, Niclas; Kaaria, Susan (World Bank, Washington, DC, 2018)
Financial inclusion of smallholder families is considered one of several key conditions needed tospark sustainable agricultural development and food security. However, an analysis of national smallholder surveys in Tanzania and Mozambique with a gender lens reveals female smallholdersremain financially excluded relative to men, despite women’s significant demand for financial services. This gender gap in financial inclusion is greatest in the wealthier smallholder households and suggests that even when wealth conditions improve only the male members overcome financial inclusion constraints. This highlights the importance of making sure that more adequate choices of formal financial products are available for female smallholders.